CANAL CAPACITY IN AREA SUMUR BATU PUMP HOUSE – CENTRAL JAKARTA - Tanjung Rahayu Raswitaningrum; Bagus Kusuma Wardana (University Of Muhammadiyah Jakarta, 2021)
Sumur Batu Pump House is located at Inpeksi Kali Sunter street, Sumur Batu Village, Kemayoran District – Central Jakarta, with coordinates 6°9'41.29